PERSEPSI MASYARAKAT MENGENAI PLTS ATAP SEBAGAI SUMBER ENERGI TERBARUKAN DI WILAYAH KOTA PEKANBARU - Sanya Gautami; Orita Mega D; Fitri Nur Astuti; Ahmad Agus W (Pelantar Press, 2023)
A technique has been developed to calculate a solar energy potential using Reanalysis data of ECMWF (ERA5) in Pekanbaru, Riau. The average of solar radiation in Pekanbaru is around 5.0 to 5.5 kWh/m in ten years. The abundant solar energy sources in Pekanbaru that can be utilized is the main factor to support developing the rooftop photovoltaic (PV) systems as a part of renewable energy. The Government’s goals of installing the PV systems are set around 3.6 GW by 2025, therefore, community participation to successful development the system is urgently needed. Considering those factors, the community's understanding and perception towards the PV system should be investigated. This research is based on a qualitative method of questionnaire and a Likert Scale Scoring will be applied to analyze the outcome. The result describes the knowledge level of community to PV systems in Pekanbaru is quite impressive for understanding of renewable energy and environmental awareness at around 86.34% and 83.79% respectively. On the other hand, the aspect of information accessibility and local campaign of PV system utilization shows a mediocre percentage at around 73.23%. Those index scores reveal the support from local governments is required for developing PV systems as one of the possible solutions to reduce greenhouse gases (GHGs)